2015
DOI: 10.1177/0954008315571682
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of poly(N-methylpyrrole) and its titanium dioxide nanocomposite film formations against equivalent electrical circuit model for the their corrosion-inhibition effects

Abstract: Conducting polymers have been used for many years as coating materials against corrosion. However, the coated materials absorb water over time resulting in reduction of resistivity and anticorrosion properties. In this study, poly( N-methylpyrrole) (P( N-MPy)) and P( N-MPy)/titanium dioxide ((TiO2) nanocomposite films were synthesized in 0.5 M oxalic acid solution on Al 1050 electrode by chronoamperometric method. The modified electrodes were characterized by scanning electron microscopy–energy dispersive X-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…Following fundamental peaks can be assigned to PMePy: 1096 cm À1 (C-H deformation) and 1056 cm À1 (C-H out-of-plane stretching). [44][45][46] As it has been reported previously, the N-substituted methyl group (C-H stretching) can show absorption around 1350-1450 cm À1 and 663 cm À1 . [46][47][48] From the spectrum, the peaks at 1451 (CH 3 asymmetric deformation) and 652 cm À1 (ring deformation with N-CH 3 stretching) are in agreement to the reported values.…”
Section: Structural Propertiessupporting
confidence: 59%
“…Following fundamental peaks can be assigned to PMePy: 1096 cm À1 (C-H deformation) and 1056 cm À1 (C-H out-of-plane stretching). [44][45][46] As it has been reported previously, the N-substituted methyl group (C-H stretching) can show absorption around 1350-1450 cm À1 and 663 cm À1 . [46][47][48] From the spectrum, the peaks at 1451 (CH 3 asymmetric deformation) and 652 cm À1 (ring deformation with N-CH 3 stretching) are in agreement to the reported values.…”
Section: Structural Propertiessupporting
confidence: 59%
“…Ates et al. found that the amount of Ti in the polypyrrole‐TiO 2 and Poly (N‐methylpyrrole) TiO 2 nanocomposites synthesized on the aluminum surface in oxalic acid solution were 0.07% and 0.04%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The IR spectrum for a case-I shows peaks at 2922 cm −2 and 2852 cm −2 which indicates the presence of -C-Hbond as stretching vibration of adhesive material whereas the peak at 1732 cm −2 confirms the presence of ester group (-COO) of adhesive material [27]. The observed peak at 1540 cm −2 represents the stretching vibrations of the alkene (C=C) group of adhesive material [28,29] whereas peaks at 1223 cm −2 and 1160 cm −2 indicate the stretching frequencies of ether (C-O) linkage [27] which can be observed from figure 2(a). The IR spectrum for case-II showed peaks at 2927 cm −2 and 2859 cm −2 indicating the stretching vibrations of the C-H bond [30,31] of activator whereas the alkene (C=C) functionality of activator [32] is observed at 1582 cm −2 .…”
Section: Ftirmentioning
confidence: 96%